Evaluation of success of alveolar cleft bone graft performed at 5 years versus 10 years of age. Issue 1 (January 2016) - Dissaux, Caroline; Bodin, Frédéric; Grollemund, Bruno; Bridonneau, Thomas; Kauffmann, Isabelle; Mattern, Jean-François; Bruant-Rodier, Catherine
Abstract: Background and purpose: Although alveolar cleft bone grafting is the most widely accepted approach, controversies remain on the operative timing. Methods: A consecutive retrospective series of 28 patients who received alveolar bone grafting was examined and divided into 2 groups depending on the age at the time of bone graft. Group A (14 patients) was operated at a mean age of 5.2 years [range, 4–7] and Group B (14 patients) at a mean age of 10 years [range, 8.5–13]. All the children were assessed clinically and by Cone Beam Computed Tomography (CBCT) before bone grafting and 6 months post-operatively. Cleft and bone graft dimensions, volumes were assessed using Osirix v.3.9.2. Residual bone graft coefficient (Bone Graft Volume on 6-months Postoperative CBCT/Alveolar Cleft Volume) was calculated. Complications, tooth movement or dental agenesis were also reported. Results: The sample was uniform within both groups, considering cleft forms, pre-surgical fistula rate and cleft volume. Residual bone graft coefficient reached 63.3% in Group A and 46.2% in Group B (p = 0.012). Results of residual bone graft are also influenced by tooth eruption through the graft (p = 0.007 in Group A and p = 0.02 in Group B). Conclusions: This 3D analysis highlighted higher success of alveolar bone grafts when children are operated earlier around 5 years. Level of evidence: Therapeutic study. Level III/retrospective comparative study.